2018
DOI: 10.3390/ijms19103168
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sodium Restriction Reduces Arterial Stiffness, Vascular TGF-β-Dependent Fibrosis and Marinobufagenin in Young Normotensive Rats

Abstract: High salt (HS) intake stimulates the production of marinobufagenin (MBG), an endogenous steroidal Na/K-ATPase ligand, which activates profibrotic signaling. HS is accompanied by a blood pressure (BP) increase in salt-sensitive hypertension, but not in normotensive animals. Here, we investigated whether HS stimulates MBG production and activates transforming growth factor-beta (TGF-β) profibrotic signaling in young normotensive rats, and whether these changes can be reversed by reducing salt to a normal salt (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…Subsequent investigations into the pathophysiological role of MBG have yielded strong evidence of an adverse effect of excessive MBG on the cardiovascular system. In animal and experimental studies, MBG was shown to promote cardiac myocyte apoptosis [ 21 ], cardiovascular fibrosis, and cardiac hypertrophy [ 15 , 16 , 17 , 39 ]. While in humans, MBG was found to be associated with autonomic activity [ 40 ], microvascular dysfunction [ 41 ], arterial stiffness [ 13 , 42 ], and increased LVMi [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent investigations into the pathophysiological role of MBG have yielded strong evidence of an adverse effect of excessive MBG on the cardiovascular system. In animal and experimental studies, MBG was shown to promote cardiac myocyte apoptosis [ 21 ], cardiovascular fibrosis, and cardiac hypertrophy [ 15 , 16 , 17 , 39 ]. While in humans, MBG was found to be associated with autonomic activity [ 40 ], microvascular dysfunction [ 41 ], arterial stiffness [ 13 , 42 ], and increased LVMi [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, while MBG is strongly associated with salt intake in normotensive rats 46 and humans, 19 and Dahl salt-sensitive hypertension, [21][22][23] more studies are needed to establish MBG as a marker of salt sen- Bold values denote significance of P < .05.…”
Section: Discussionmentioning
confidence: 99%
“…tion44 and vascular fibrosis,45,46 respectively, ultimately impairing vasorelaxation. In support, Fedorova et al have demonstrated impaired sodium nitroprusside-induced vasorelaxation of rat aortic explants pretreated with MBG.…”
mentioning
confidence: 99%
“…In normotensive rats, high dietary salt intake have been associated with the activation of TGF-β signaling within the arterial wall and increased aortic stiffness in the presence of elevated levels of the Na/K-ATPase ligand MBG despite unchanged blood pressure [43]. Moreover, the rats exposed to a reduced salt diet after the period of high salt intake exhibited a decrease in MBG levels, downregulation of the pro-fibrotic TGF-β pathway, a decrease of aortic wall collagen content and normalization of the pulse wave velocity to control levels.…”
Section: Marinobufagenin and Fibrosismentioning
confidence: 99%
“…Moreover, the rats exposed to a reduced salt diet after the period of high salt intake exhibited a decrease in MBG levels, downregulation of the pro-fibrotic TGF-β pathway, a decrease of aortic wall collagen content and normalization of the pulse wave velocity to control levels. The authors also demonstrated that MBG stimulates collagen production in parallel with activation of TGF-β in cultured VSMCs in vitro, in the absence of hemodynamic effects [43]. Lowering the salt intake can improve vascular elasticity and decrease the cardiovascular risk by reducing the plasma MBG concentration.…”
Section: Marinobufagenin and Fibrosismentioning
confidence: 99%